Reno-portal shunt for liver transplant, an alternative inflow for recipients with grade III–IV portal vein thrombosis: Tips for a better outcome. (2017) - Nazzal, Mustafa; Sun, Yifei; Okoye, Obi; Diggs, Laurence; Evans, Neil; Osborn, Tamara; Etesami, Kambiz; Varma, Chintalapati
Highlights: Grade III, IV Portal vein thrombosis Poses a Great challenge to orthotopic liver transplantation. We present two cases of reno-portal anastomosis to establish inflow to the new liver allograft. Meticulous preoperative planning with triple phase CT to measure the diameter of spleno-renal shunt, along with Duplex scan confirming antegrade flow towards the renal vein is essential for a better outcome. Abstract: Introduction: Portal vein thrombosis (PVT) poses an extremely difficult problem in cirrhotic patients who are in need of a liver transplant. The prevalence of PVT in patients with cirrhosis ranges from 0.6% to 26% Nery et al. (2015) [1]. The presence of PVT is associated with more technically difficult liver transplant and in certain cases can be a contraindication to liver transplant. The only option for these patients with extensive PVT would be a multi-visceral transplant, the later unfortunately has a much higher morbidity and mortality compared to liver only transplant Smith et al. (2016) [2]. An alternative approach is needed to provide a safe and reliable outcome. Presentation of case: In this case series, we present our experience with reno-portal shunt as an alternative inflow for the liver allograft. Discussion: This approach appears to be safe with good long-term outcome.Although this technique has been described before, we provide additional considerations that produced good outcomes in our patients. Conclusion: We believe that meticulous preoperative planning with high-resolution triple phase CT imaging with a measurement of the diameter of the spleno-renal shunt along with a duplex scan measuring flow through the shunt is key to a successful transplantation. Moreover, appropriate donor liver size is also of extreme importance to avoid portal hypoperfusion.